Online Efl Teaching At The University Level In Bangladesh During Covid-19 Pandemic Practices, Challenges And Coping Strategies. - Hasan, Md Mahamudul (2024)
History of English language teaching in Bangladesh traces back to the colonial times, but it never had any experience of online teaching before the onslaught of COVID-19 in March 2019. The country, like many other developing countries of the world, had to shift to online mode of teaching very suddenly immediately after the rapid and wide spread of the deadly pandemic with no previous experience and without much preparation of teachers and learners. English teaching at the university level in Bangladesh also suffered serious setbacks during this period and went through massive transformations. It is important to note that as English is a priority area of education in Bangladesh, like all other English as a Foreign language (EFL), English as a second language (ESL) and English as an international language (EIL) context. There was no alternative to continuing teaching English in the online mode during the pandemic. English being an important global language used internationally for both academic and professional purposes both at home and abroad, its teaching and learning need to be continued in all situations, at all costs. The only way to do it during the pandemic was the online mode. However, for doing it effectively, it has been essential to examine the various ways of online teaching of English. As it was new, how effective online teaching of English proved, what challenges were being faced by teachers and what strategies they adopted for overcoming the challenges need close and critical examination. In the meantime, some studies have already been done on online teaching in the country during the pandemic and beyond, but no significant study has been done on the practices, effectiveness, challenges and coping strategies of teaching English with a strong theoretical back-up and scientific design.